ELECTRIFIED MOBILITY AS AN ENGINE OF SUSTAINABLE ECONOMIC GROWTH: EVIDENCE ON THE ROLE OF TRANSPORT INFRASTRUCTURE (Ustozlar uchun, 2026)
This study explores electrified mobility as a driver of sustainable economic growth, with particular attention to the mediating role of transport infrastructure. It investigates how infrastructure such as EV charging stations, electrified rail, smart energy systems, and integrated transport networks shapes the economic and environmental outcomes of transport modernization. Existing evidence indicates that transport infrastructure investment can promote economic growth, while sustainability outcomes vary by transport mode, with rail generally associated with lower environmental harm than road- and air-based expansion. The growing importance of EV charging infrastructure and renewable energy integration further suggests that electrified mobility can strengthen productivity and connectivity while supporting decarbonization goals. This topic is relevant to policymakers and researchers seeking to understand how transport electrification can generate long-term economic value without intensifying environmental degradation.